Da flor ao Rivotril: o homoerotismo em Júlio Barbabella e Júnior Ratts - Silva, Matheus Araújo de Souza (2023)
This master’s thesis studies the body, the enjoyment and the blood as distinguishing features of the contemporary Brazilian homoerotic literature in the antinovels Jaz Mim (1992), by Júlio Barbabella and O homem com alma Rivotril (2018), by Júnior Ratts. The homoeroticism permeates these texts as part of an enduring curse since they are narratives that display problematic protagonists doomed to martyrdom. This study develops a criticism on the morbid representation of homosexuality in order to understand why it is shown associated with shame, fear, rejection and pain. Additionally, it aims to investigate how these feelings contribute to the ailment and death of the characters. The outcomes from such readings allowed us to infer that the sexualities of these men are responsible for the decline of their lives as they are under the influence of the closet, an artifact of dichotomous compartments that has ruled those who dare to subvert the heteronormative hegemony. The reading of this master’s thesis shows that the closet, as a power device, casts upon the characters the rejection of themselves in the face of their identities, wills and desires. Although eroticism is the antagonistic force that hinders the action of the closet and its agents, this brings the tension to the characters, and it exposes them to the conflict of the denial of the self against the precipitation of the erotic. Death, be it the decline of the body, the enjoyment, or the representation of the vital finitude, presents itself in the two texts as the spinal cord of the homosexual existence, because the transgression, in the literary context, is corrected through the sacrifice of life. The gay body is object of negligence, reduced to the cathartic element. Therefore, an autopsy of sufferings was necessary so that it could be defined another way of thinking homoerotic performances beyond these texts about lives falling apart. Among the texts that supported this theoretical framework, the works of Georges Bataille (1987), João Silvério Trevisan (2018), James N. Green (2018), Anselmo Alós (2017), Michel Foucault (2018), Eve Sedgwick (2007), Daniel Borillo (2016), Susan Sontag and Sigmund Freud (2013) are underlined.